Validation of Lecturer Competency Model on E-Learning in Medan State University - Rafael Lisinus Ginting; Albert Pauli Sirait; Elizon Nainggolan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The policy of maintaining physical distance during the Pandemic made every lecturer to conduct e-learning so that learning continued. This certainly forces lecturers to improve their competence. To determine the success of this learning system, an evaluation of the process and competence of lecturers in implementing e-learning is carried out. This study aims to determine the profile of the implementation of e-learning in the Faculty of Education during the Pandemic and to validate the competency model framework of lecturers in managing e-learning. Validation of this competency model is carried out using the Delphi method. The instrument used was a questionnaire containing a list of competency indicators that included planning and preparation, learning environment, instruction in learning, professional responsibility. The research panelists were 5 experts in the development of e-learning based on their experiences, research and scientific publications, 10 lecturers who used to organize e-learning, and 15 students who did e-learning. Panelists are asked to provide an assessment of the list of competencies provided. This research was conducted in three Delphi rounds. The first round produced 100 competency indicators with an 82% approval rate. in the second round, the competent indicator changed to 68 indicators with an approval rate of 90%. In the final round, this study succeeded in validating 40 models of lecturer competence in conducting e-learning. All of the competency models were approved by all panelists with an approval rate reaching 100%. The implementation of e-learning does not only focus on placing students at the center of the learning process but must still focus on learning objectives. The application of this competency model needs to consider several things related to the following matters. As for what needs to be considered is the readiness of the lecturers themselves in conducting e-learning which is marked by their competencies, as well as the availability of other supporting devices.